Protective glass

By reasonably designing the composition and composition ratio of protective glass, the problem of insufficient radiation stability and density of protective glass in the prior art has been solved, and more efficient radiation protection and equipment miniaturization have been achieved.

CN119797753APending Publication Date: 2025-04-11CDGM GLASS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022077.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing solar protective glass has poor radiation stability and low density, which leads to the equipment requiring thicker glass, thereby increasing the volume and operation and maintenance costs of the equipment.

Method used

By rationally designing the composition of protective glass, it contains components such as SiO2, BaO, B2O3, MgO, ZnO, CaO, La2O3, CeO2, TeO2, etc., and the proportion of each component is controlled to achieve excellent irradiation stability and high density.

Benefits of technology

The radiation stability and density of protective glass have been improved, which reduces the thickness requirement of glass, promotes the miniaturization of space equipment, and reduces operation and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231669650000081
    Figure BDA0005231669650000081
  • Figure BDA0005231669650000091
    Figure BDA0005231669650000091
  • Figure BDA0005231669650000092
    Figure BDA0005231669650000092
Patent Text Reader

Abstract

Provided is a cover glass having excellent irradiation stability and high density. The protective glass comprises the following components in percentage by weight: 8.0 to 50.0 percent of SiO2; 10.0% to 40.0% of BaO (barium oxide); 3.0% to 30.0% of B2O3; 1.0 to 15.0 percent of MgO; 1.0 to 15.0 percent of ZnO (zinc oxide); 1.0 to 15.0 percent of CaO; 1.0 to 30.0 percent of La2O3 (La2O3); 1.0 to 7.0 percent of CeO2; and 0.1 to 5.0 percent of TeO2. Through reasonable component design, the protective glass disclosed by the invention has excellent irradiation stability and relatively high density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a protective glass, in particular to a protective glass with excellent radiation stability and high density. Background Art

[0002] Solar protection cover glass can effectively block the radiation of high-energy particles and rays from space to aircraft and solar cells, and protect solar cells from space ion radiation. Therefore, solar protection glass is an important guarantee for the energy supply of space equipment. The radiation stability of solar protection glass in the prior art is poor and the density is low. In order to achieve the protection effect, the glass used in space equipment is thicker, resulting in a larger equipment volume, thereby increasing the launch and operation and maintenance costs of the equipment. Therefore, increasing the glass density and improving the radiation stability can reduce the thickness of the protective glass of space equipment, which is of great significance to the miniaturization of space equipment. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a protective glass with excellent radiation stability and high density.

[0004] The technical solution adopted by the present invention to solve the technical problem is:

[0005] Protective glass, its components expressed in weight percentage, contains: SiO 2 : 8.0~50.0%; BaO: 10.0~40.0%; B 2 O 3 : 3.0~30.0%; MgO: 1.0~15.0%; ZnO: 1.0~15.0%; CaO: 1.0~15.0%; La 2 O 3 :1.0~30.0%;CeO 2 :1.0~7.0%;TeO 2 :0.1~5.0%.

[0006] Furthermore, the protective glass, expressed in weight percentage, also contains: Al 2 O 3 :0~10.0%;and / or Y 2 O 3 :0~10.0%;and / or Gd 2 O 3 :0~10.0%;and / or ZrO 2 :0~10.0%;and / or Sb 2 O 3 :0~2.0%;and / or R 2 O: 0-10.0%, R 2 O is Li 2O、Na 2 O.K 2 One or more of O.

[0007] Protective glass, its components expressed in weight percentage, consists of SiO 2 : 8.0~50.0%; BaO: 10.0~40.0%; B 2 O 3 : 3.0~30.0%; MgO: 1.0~15.0%; ZnO: 1.0~15.0%; CaO: 1.0~15.0%; La 2 O 3 :1.0~30.0%;CeO 2 :1.0~7.0%;TeO 2 :0.1~5.0%;Al 2 O 3 :0~10.0%;Y 2 O 3 :0~10.0%;Gd 2 O 3 :0~10.0%; ZrO 2 :0~10.0%; Sb 2 O 3 :0~2.0%; R 2 O: 0 to 10.0%, the R 2 O is Li 2 O、Na 2 O.K 2 One or more of O.

[0008] Furthermore, the components of the protective glass are expressed in weight percentage, wherein:

[0009] (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is 0.2 to 1.2, preferably

[0010] (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO2 +B 2 O 3 +Al 2 O 3 ) is 0.2 to 1.0, and more preferably (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is 0.2 to 0.8, and more preferably (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is 0.4~0.7.

[0011] Furthermore, the components of the protective glass are expressed in weight percentage, wherein: CeO 2 / Sb 2 O 3 5.0~50.0, preferably CeO 2 / Sb 2 O 3 5.0 to 40.0, more preferably CeO 2 / Sb 2 O 3 7.0 to 25.0, more preferably CeO 2 / Sb 2 O 3 It is 9.0~23.0.

[0012] Furthermore, the components of the protective glass are expressed in weight percentage, wherein: TeO 2 / Sb 2 O 3 0.3 to 6.0, preferably TeO 2 / Sb 2 O 3 0.5 to 4.0, more preferably TeO 2 / Sb 2 O 3 is 1.0 to 3.5, and TeO is more preferred2 / Sb 2 O 3 is 1.5 to 2.7.

[0013] Furthermore, for the protective glass described above, its components are expressed in weight percentages, where: SiO 2 : 10.0 to 35.0%, preferably SiO 2 : 15.0 to 30.0%, more preferably SiO 2 : 20.0 to 25.0%; and / or BaO: 20.0 to 40.0%, preferably BaO: 25.0 to 35.0%, more preferably BaO: 23.0 to 30.0%; and / or B 2 O 3 : 3.0 to 25.0%, preferably B 2 O 3 : 3.0 to 20.0%, more preferably B 2 O 3 : 4.0 to 13.0%; and / or MgO: 2.0 to 12.0%, preferably MgO: 3.0 to 11.0%, more preferably MgO: 5.0 to 10.0%; and / or ZnO: 1.0 to 12.0%, preferably ZnO: 2.0 to 10.0%, more preferably ZnO: 2.0 to 8.0%; and / or CaO: 1.0 to 12.0%, preferably CaO: 2.0 to 10.0%, more preferably CaO: 2.0 to 8.0%; and / or La 2 O 3 : 2.0 to 20.0%, preferably La 2 O 3 : 2.0 to 10.0%, more preferably La 2 O 3 : 2.0 to 5.0%; and / or CeO 2 : 1.0 to 6.0%, preferably CeO 2 : 3.0 to 6.0%, more preferably CeO 2 : 4.5 to 5.5%; and / or Al 2 O 3 : 0 to 8.0%, preferably Al 2 O 3 : 0 to 6.0%, more preferably Al 2 O 3 : 1.0 to 5.0%; and / or Y 2 O 3 : 0 to 8.0%, preferably Y 2 O 3 : 1.0 to 6.0%, more preferably Y 2 O 3 : 2.0 to 5.0%; and / or Gd 2 O3 : 0-8.0%, preferably Gd 2 O 3 : 1.0 to 6.0%, more preferably Gd 2 O 3 :2.0~6.0%;and / or ZrO 2 : 0~8.0%, preferably ZrO 2 : 1.0 to 7.0%, more preferably ZrO 2 :3.0~7.0%;and / or Sb 2 O 3 : 0.05~1.5%, preferably Sb 2 O 3 : 0.1 to 1.0%, more preferably Sb 2 O 3 :0.2~0.5%;and / or TeO 2 : 0.1~4.0%, preferably TeO 2 : 0.1-2.0%, more preferably TeO 2 :0.2~1.0%;and / or R 2 O: 0-5.0%, preferably R 2 O: 0 to 2.0%, preferably no R 2 O, R 2 O is Li 2 O、Na 2 O.K 2 One or more of O.

[0014] Furthermore, the elastic modulus of the protective glass is greater than 80 GPa, preferably greater than 85 GPa, and more preferably greater than 90 GPa; and / or the density ρ is 3.50 g / cm 3 Above, preferably 3.60 g / cm 3 More preferably, 3.70 g / cm 3 and / or the light transmittance of protective glass with a thickness of less than 0.5 mm τ 500nm It is 85% or more, preferably 86% or more, more preferably 86-92%; and / or the average irradiation stability Δτ of the protective glass with a thickness of 0.5 mm or less at 500-2000 nm is 0.7% or less, preferably 0.6%, more preferably 0.5% or less.

[0015] The glass element is made of the above-mentioned protective glass.

[0016] A device comprising the above-mentioned protective glass or the above-mentioned glass element.

[0017] The beneficial effects of the present invention are: through reasonable component design, the protective glass of the present invention has excellent radiation stability and high density, can effectively protect against space rays, and is conducive to reducing the thickness of the protective glass of space equipment and realizing the miniaturization of space equipment. DETAILED DESCRIPTION

[0018] The embodiments of the protective glass of the present invention are described in detail below, but the present invention is not limited to the embodiments described below, and can be implemented with appropriate changes within the scope of the purpose of the present invention. In addition, although the description of the repeated description may be appropriately omitted, the gist of the invention is not limited thereto. In the following content, the protective glass of the present invention is sometimes referred to as glass.

[0019] [Protective glass]

[0020] The range of each component (ingredient) of the protective glass of the present invention is explained below. In the present invention, unless otherwise specified, the content, total content, and total content of each component are all expressed in weight percentage (wt%), that is, the content, total content, and total content of each component are expressed as a weight percentage relative to the total amount of glass material converted into an oxide composition. Here, the "composition converted into oxides" means that when the oxides, complex salts, hydroxides, etc. used as raw materials for the protective glass composition of the present invention decompose and convert into oxides during melting, the total amount of the oxide material is taken as 100%.

[0021] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0022] <Essential Components and Optional Components>

[0023] SiO 2 As a glass former, it forms the skeleton of glass and can improve the thermal stability, chemical stability and elastic modulus of glass. However, if SiO 2 Too much SiO will make the glass more difficult to melt and clarify, and reduce the density of the glass. 2 The content of is 8.0 to 50.0%, preferably 10.0 to 35.0%, more preferably 15.0 to 30.0%, further preferably 20.0 to 25.0%.

[0024] BaO can reduce the viscosity of glass, increase the density and elastic modulus of glass, and have a good shielding effect on space rays; however, if the content of BaO is too much, the transmittance of glass will decrease, and the chemical stability and thermal stability will deteriorate. Therefore, the content of BaO is 10.0-40.0%, preferably 20.0-40.0%, more preferably 25.0-35.0%, and further preferably 23.0-30.0%.

[0025] B 2 O 3 As a glass former, it can enter the network to improve the glass forming properties, reduce the expansion coefficient, viscosity and softening temperature of the glass, and improve the elastic modulus and radiation protection ability of the glass; but if B 2 O 3 If the content of B is too high, the transmittance of the glass will decrease, the thermal stability and chemical stability will deteriorate, and the density of the glass will decrease. 2 O 3 The content of is 3.0 to 30.0%, preferably 3.0 to 25.0%, more preferably 3.0 to 20.0%, and further preferably 4.0 to 13.0%.

[0026] MgO can improve the transmittance of glass, improve the chemical stability of glass, improve the elastic modulus, density and radiation protection ability of glass; however, if the content of MgO is too much, the radiation stability of glass will be reduced. Therefore, the content of MgO is 1.0-15.0%, preferably 2.0-12.0%, more preferably 3.0-11.0%, and further preferably 5.0-10.0%.

[0027] In the glass of the present invention, ZnO can improve the transmittance of the glass, increase the chemical stability of the glass, and improve the elastic modulus, density and radiation protection ability; however, if the content of ZnO is too much, the surface tension of the glass is large and it is difficult to eliminate bubbles. Therefore, the content of ZnO is 1.0-15.0%, preferably 1.0-12.0%, more preferably 2.0-10.0%, and further preferably 2.0-8.0%.

[0028] CaO can improve the elastic modulus and radiation protection ability of glass; however, if the content of CaO is too much, the radiation stability of glass will be reduced. Therefore, the content of CaO is 1.0-15.0%, preferably 1.0-12.0%, more preferably 2.0-10.0%, and further preferably 2.0-8.0%.

[0029] La 2 O 3 As a network intermediate, it can improve the structural tightness of glass, improve the density, elastic modulus and radiation protection ability of glass; but if La 2 O 3If the content of La is too high, the radiation stability, transmittance and thermal stability of the glass will decrease. 2 O 3 The content of is 1.0 to 30.0%, preferably 2.0 to 20.0%, more preferably 2.0 to 10.0%, further preferably 2.0 to 5.0%.

[0030] CeO 2 It has good radiation resistance, preventing the glass from losing transmittance under space radiation. 2 It is also a good clarifier and helps eliminate bubbles; but CeO 2 Too much CeO will cause the glass transmittance to decrease significantly. 2 The content of is 1.0 to 7.0%, preferably 1.0 to 6.0%, more preferably 3.0 to 6.0%, further preferably 4.5 to 5.5%.

[0031] Al 2 O 3 As a network intermediate, it can increase the stability of the glass network, improve the elastic modulus, and improve the glass properties; but if Al 2 O 3 Too much Al will increase the difficulty of melting the glass. 2 O 3 The content of is 0 to 10.0%, preferably 0 to 8.0%, more preferably 0 to 6.0%, further preferably 1.0 to 5.0%.

[0032] Y 2 O 3 It can improve the glass's resistance to devitrification, increase the glass's density and elastic modulus; but if Y 2 O 3 If the content of Y is too high, the chemical stability of the glass will decrease. 2 O 3 The content of is 0 to 10.0%, preferably 0 to 8.0%, more preferably 1.0 to 6.0%, further preferably 2.0 to 5.0%.

[0033] G 2 O 3 It can improve the radiation protection ability and devitrification resistance of glass, and increase the density and elastic modulus of glass; but if Gd 2 O 3 If the content of Gd is too high, the anti-devitrification ability of the glass will decrease. 2 O 3 The content of is 0 to 10.0%, preferably 0 to 8.0%, more preferably 1.0 to 6.0%, further preferably 2.0 to 6.0%.

[0034] ZrO 2 It can improve the chemical stability, density, elastic modulus and radiation protection of glass, but if its content is too high, it will be difficult for the glass to melt. 2 The content of is 0 to 10.0%, preferably 0 to 8.0%, more preferably 1.0 to 7.0%, further preferably 3.0 to 7.0%.

[0035] The inventors have found through a large number of experiments that in some embodiments, La 2 O 3 , Y 2 O 3 、ZrO 2 , Gd 2 O 3 Total content La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 With SiO 2 , B 2 O 3 、Al 2 O 3 Total content of SiO 2 +B 2 O 3 +Al 2 O 3 The ratio between 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is controlled within the range of 0.2 to 1.2, the glass has a high transmittance and elastic modulus, a high density, and good thermal stability. Therefore, it is preferred that (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3) is 0.2 to 1.2, and more preferably (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) /

[0036] (SiO 2 +B 2 O 3 +Al 2 O 3 ) is 0.2 to 1.0, and more preferably (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is 0.2 to 0.8, and more preferably (La 2 O 3 +Y 2 O 3 +ZrO 2 +Gd 2 O 3 ) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is 0.4~0.7.

[0037] Sb 2 O 3 It is a good clarifier, which is beneficial to the escape of gas in glass and TeO 2 Using them in combination in a certain proportion can effectively increase the CeO 2 The transmittance of glass; but if Sb 2 O 3 If the content of Sb is too high, the radiation stability of the glass will decrease. 2 O 3 The content of is 0 to 2.0%, preferably 0.05 to 1.5%, more preferably 0.1 to 1.0%, and further preferably 0.2 to 0.5%.

[0038] In some embodiments, CeO 2 The content of Sb 2 O 3 The ratio between the content of CeO2 / Sb 2 O 3 Controlling it within the range of 5.0 to 50.0 can make the glass have good transmittance and excellent radiation stability. 2 / Sb 2 O 3 5.0 to 50.0, more preferably CeO 2 / Sb 2 O 3 5.0 to 40.0, more preferably CeO 2 / Sb 2 O 3 7.0 to 25.0, and CeO is more preferred 2 / Sb 2 O 3 It is 9.0~23.0.

[0039] TeO 2 It can improve the radiation protection ability and devitrification resistance of glass, increase the density and elastic modulus of glass, and Sb 2 O 3 Using them in combination in a certain proportion can effectively increase the CeO 2 The transmittance of glass, but if the content is too high, the anti-devitrification ability of glass will decrease. 2 The content of is 0.1 to 5.0%, preferably 0.1 to 4.0%, more preferably 0.1 to 2.0%, further preferably 0.2 to 1.0%.

[0040] In some embodiments, TeO 2 The content of Sb 2 O 3 The ratio between the content of TeO 2 / Sb 2 O 3 Controlling it within the range of 0.3 to 6.0 can improve the light transmittance of the glass and prevent the radiation stability of the glass from deteriorating. 2 / Sb 2 O 3 0.3 to 6.0, more preferably TeO 2 / Sb 2 O 3 is 0.5 to 4.0, and TeO is more preferred 2 / Sb 2 O 3 1.0 to 3.5, more preferably TeO 2 / Sb 2 O 3 It is 1.5 to 2.7.

[0041] R 2 O(R 2 O is Li 2 O、Na 2 O.K 2 O) can reduce the viscosity of glass, making it easier to melt and clarify the glass, but if its content is too high, the density and elastic modulus of the glass will be significantly reduced. 2 The content of O is 0 to 10.0%, preferably 0 to 5.0%, and more preferably 0 to 2.0%. In some embodiments, it is further preferred that R 2 O.

[0042] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the protective glass of the present invention; however, as raw materials and / or equipment for producing protective glass, there may be certain impurities or components that are not intentionally added, which may be contained in small amounts or trace amounts in the final protective glass, and this situation is also within the scope of protection of the patent of this invention.

[0043] Next, the performance of the cover glass of the present invention will be described.

[0044] <Light transmittance>

[0045] Light transmittance of glass (τ 500nm ) The test shall be carried out according to the method specified in GB / T 7962.12-2010.

[0046] In some embodiments, the light transmittance (τ 500nm ) is 85% or more, preferably 86% or more, more preferably 86 to 92%.

[0047] The thickness of the glass is preferably 0.05 to 0.5 mm, more preferably 0.1 to 0.4 mm, and even more preferably 0.1 mm, 0.2 mm, or 0.3 mm.

[0048] <Radiation stability>

[0049] The radiation stability of glass is tested according to the method specified in "GJB 1976A-2021 Specification for Radiation-resistant Glass Cover for Space Use".

[0050] In some embodiments, the average radiation stability (Δτ) of the protective glass of the present invention with a thickness of 0.5 mm or less at 500 to 2000 nm is 0.7% or less, preferably 0.6%, and more preferably 0.5% or less.

[0051] The thickness of the glass is preferably 0.05 to 0.5 mm, more preferably 0.1 to 0.4 mm, and even more preferably 0.1 mm, 0.2 mm, or 0.3 mm.

[0052] <Elastic modulus>

[0053] The elastic modulus of glass is tested according to the method specified in GB / T 7962.6-2010.

[0054] In some embodiments, the elastic modulus of the protective glass of the present invention is 80 GPa or more, preferably 85 GPa or more, and more preferably 90 GPa or more.

[0055] Increasing the elastic modulus of protective glass will help reduce the difficulty of processing the glass into curved shapes.

[0056] <density>

[0057] The density (ρ) of protective glass is tested according to the method specified in GB / T7962.20-2010.

[0058] In some embodiments, the density (ρ) of the protective glass of the present invention is 3.50 g / cm 3 Above, preferably 3.60 g / cm 3 More preferably, 3.70 g / cm 3 above.

[0059] Due to the above-mentioned excellent properties, the protective glass of the present invention can be used to manufacture glass components (such as protective glass sheets, protective glass cover plates, etc.), and the glass components of the present invention can have any useful shape or thickness. The protective glass or glass components of the present invention can be widely used in various types of equipment, including but not limited to spacecraft, solar cells, aircraft, etc.

[0060] [Manufacturing method of protective glass]

[0061] The manufacturing method of the protective glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1500°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0062] Example

[0063] <Protective Glass Example>

[0064] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.

[0065] In this embodiment, the protective glass having the composition shown in Tables 1 to 3 is obtained by using the above-mentioned protective glass manufacturing method. In addition, the properties of each glass are measured by the test method described in the present invention, and the test results are shown in Tables 1 to 3. In the following embodiments, the thickness of the test sample for the radiation stability and light transmittance of the protective glass is 0.2 mm.

[0066] Table 1.

[0067]

[0068]

[0069] Table 2.

[0070]

[0071]

[0072] Table 3.

[0073]

Claims

1. Protective glass, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 8.0-50.0%; BaO: 10.0~40.0%; B2O3: 3.0~30.0%; MgO: 1.0~15.0%; ZnO: 1.0~15.0%; CaO: 1.0~15.0%; La2O3: 1.0~30.0%; CeO2: 1.0~7.0%; TeO2: 0.1~5.0%.

2. The protective glass according to claim 1, characterized in that: Its components are expressed in weight percentage and also contain: Al2O3: 0-10.0%; and / or Y2O3: 0-10.0%; and / or Gd2O3: 0-10.0%; and / or ZrO2: 0-10.0%; and / or Sb2O3: 0-2.0%; and / or R2O: 0-10.0%, wherein R2O is one or more of Li2O, Na2O, and K2O.

3. Protective glass, characterized in that: Its components, expressed in weight percentage, are SiO2: 8.0-50.0%; BaO: 10.0~40.0%; B2O3: 3.0~30.0%; MgO: 1.0~15.0%; The invention relates to a novel nanostructured carbon nanotube film comprising: ZnO: 1.0-15.0%; CaO: 1.0-15.0%; La2O3: 1.0-30.0%; CeO2: 1.0-7.0%; TeO2: 0.1-5.0%; Al2O3: 0-10.0%; Y2O3: 0-10.0%; Gd2O3: 0-10.0%; ZrO2: 0-10.0%; Sb2O3: 0-2.0%; and R2O: 0-10.0%, wherein R2O is one or more of Li2O, Na2O, and K2O.

4. The protective glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (La2O3+Y2O3+ZrO2+Gd2O3) / (SiO2+B2O3+Al2O3) is 0.2-1.2, preferably (La2O3+Y2O3+ZrO2+Gd2O3) / (SiO2+B2O3+Al2O3) is 0.2-1.0, more preferably (La2O3+Y2O3+ZrO2+Gd2O3) / (SiO2+B2O3+Al2O3) is 0.2~0.8, and it is more preferred that (La2O3+Y2O3+ZrO2+Gd2O3) / (SiO2+B2O3+Al2O3) is 0.4~0.

7.

5. The protective glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: CeO2 / Sb2O3 is 5.0-50.0, preferably CeO2 / Sb2O3 is 5.0-40.0, more preferably CeO2 / Sb2O3 is 7.0-25.0, and further preferably CeO2 / Sb2O3 is 9.0-23.

0.

6. The protective glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: TeO2 / Sb2O3 is 0.3-6.0, preferably TeO2 / Sb2O3 is 0.5-4.0, more preferably TeO2 / Sb2O3 is 1.0-3.5, and further preferably TeO2 / Sb2O3 is 1.5-2.

7.

7. The protective glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 10.0-35.0%, preferably SiO2: 15.0-30.0%, more preferably SiO2: 20.0-25.0%; and / or BaO: 20.0-40.0%, preferably BaO: 25.0-35.0%, more preferably BaO: 23.0-30.0%; and / or B2O3: 3.0-25.0%, preferably B2O3: 3.0-20.0%, more preferably B2O3: 4.0-13.0%; and / or MgO: 2.0-12.0%, preferably MgO: 3.0-11.0%, more preferably MgO: 5.0-10.0%; and / or ZnO: 1.0-12.0%, preferably ZnO: 2.0-10.0%, more preferably ZnO: 2.0-8.0%; and / or CaO: 1.0-12.0%, preferably CaO: 2.0-10.0%, more preferably CaO: 2.0-8.0%; and / or La2O3: 2.0-20.0%, preferably La2O3: 2.0-10.0%, more preferably La2O3: 2.0-5.0%; and / or CeO2: 1.0-6.0%, preferably Select CeO2: 3.0-6.0%, more preferably CeO2: 4.5-5.5%; and / or Al2O3: 0-8.0%, preferably Al2O3: 0-6.0%, more preferably Al2O3: 1.0-5.0%; and / or Y2O3: 0-8.0%, preferably Y2O3: 1.0-6.0%, more preferably Y2O3: 2.0-5.0%; and / or Gd2O3: 0-8.0%, preferably Gd2O3: 1.0-6.0%, more preferably Gd2O3: 2.0-6.0%; and / or ZrO2: 0-8.0%, preferably Z rO2: 1.0-7.0%, more preferably ZrO2: 3.0-7.0%; and / or Sb2O3: 0.05-1.5%, preferably Sb2O3: 0.1-1.0%, more preferably Sb2O3: 0.2-0.5%; and / or TeO2: 0.1-4.0%, preferably TeO2: 0.1-2.0%, more preferably TeO2: 0.2-1.0%; and / or R2O: 0-5.0%, preferably R2O: 0-2.0%, more preferably does not contain R2O, and the R2O is one or more of Li2O, Na2O, and K2O.

8. The protective glass according to any one of claims 1 to 3, characterized in that: The elastic modulus of the protective glass is greater than 80 GPa, preferably greater than 85 GPa, and more preferably greater than 90 GPa; and / or the density ρ is 3.50 g / cm 3 Above, preferably 3.60 g / cm 3 More preferably, 3.70 g / cm 3 and / or the light transmittance of protective glass with a thickness of less than 0.5 mm τ 500nm It is 85% or more, preferably 86% or more, more preferably 86-92%; and / or the average irradiation stability Δτ of the protective glass with a thickness of 0.5 mm or less at 500-2000 nm is 0.7% or less, preferably 0.6%, more preferably 0.5% or less.

9. A glass element, characterized in that Made of the protective glass described in any one of claims 1 to 8.

10. A device, characterized in that: A protective glass according to any one of claims 1 to 8, or a glass element according to claim 9.